Legal mechanisms for drug prevention between international frameworks and the Algerian approach in the light of Law 23-05 - KAHOUL, Roumeissa; BOUHOUCHE, Hichem (Journal of Human Sciences, 2025)
The prevention of drugs and the treatment of this phenomenon requires the concerted of a set of international and national efforts, and this can only be achieved by legal coordination between the various official and civil bodies, with the aim of activating the legislative and regulatory Legal texts related to the prevention of narcotic drugs and psychotropic substances. the Algerian legislator to combat this dangerous phenomenon that has spread terribly within Algerian society, where he worked to develop a stack of laws related to the prevention of drugs and substances. Starting with Ordinance 66-155 With regard to the Penal Code, and until the promulgation of Law No. 23-05 amending and supplementing Law No 04-18 on the prevention of narcotic drugs and psychotropic substances and the combating of their illicit use and trafficking, these legislations constituted the governing legal framework in this field the legislator has drawn up a criminal policy to combat drug crimes in line with international developments.